2014
DOI: 10.1142/s0217751x1430049x
|View full text |Cite
|
Sign up to set email alerts
|

Review of the holographic Lifshitz theory

Abstract: We review interesting results achieved in recent studies on the holographic Lifshitz field theory. The holographic Lifshitz field theory at finite temperature is described by a Lifshitz black brane geometry. The holographic renormalization together with the regularity of the background metric allows to reproduce thermodynamic quantities of the dual Lifshitz field theory where the Bekenstein-Hawking entropy appears as the renormalized thermal entropy. All results satisfy the desired black brane thermodynamics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…where φ andã i represent a dilaton and two axion fields and L is the AdS radius. Following the AdS/CFT correspondence, the profile of the dilaton field can be reinterpreted as a nontrivial running scaling [32,33,51,35,52,37], while the bulk gauge field describes a certain fermionic matter like quark [38]. This means that the gravity theory we consider mimics a nonconformal medium composed of fermions and gauge bosons [39,40].…”
Section: Einstein-maxwell-dilaton-axion Modelmentioning
confidence: 99%
“…where φ andã i represent a dilaton and two axion fields and L is the AdS radius. Following the AdS/CFT correspondence, the profile of the dilaton field can be reinterpreted as a nontrivial running scaling [32,33,51,35,52,37], while the bulk gauge field describes a certain fermionic matter like quark [38]. This means that the gravity theory we consider mimics a nonconformal medium composed of fermions and gauge bosons [39,40].…”
Section: Einstein-maxwell-dilaton-axion Modelmentioning
confidence: 99%
“…Motivated by * Electronic address: wbrenna@uwaterloo.ca † Electronic address: rbmann@uwaterloo.ca ‡ Electronic address: miokpark@kias.re.kr the hope of obtaining a duality between condensed matter physics with quantum criticality, the anisotropic scaling properties of these systems imply from gauge-gravity duality that the bulk spacetime geometry likewise asymptotes to a spacetime with the same scaling properties [42]. Known as Lifshitz spacetimes, they remain a subject of intensive study [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by * Electronic address: wbrenna@uwaterloo.ca † Electronic address: rbmann@uwaterloo.ca ‡ Electronic address: miokpark@kias.re.kr the hope of obtaining a duality between condensed matter physics with quantum criticality, the anisotropic scaling properties of these systems imply from gauge-gravity duality that the bulk spacetime geometry likewise asymptotes to a spacetime with the same scaling properties [42]. Known as Lifshitz spacetimes, they remain a subject of intensive study [43][44][45][46].We seek to understand the thermodynamics of Lifshitz black holes [47][48][49] in the context of extended phase space, particularly the notion of mass as enthalpy [13]. Mass, a difficult concept to define in general relativity, is even more problematic when higher-curvature and/or differing asymptotics are incorporated.…”
mentioning
confidence: 99%
“…When one applies the holographic renormalization technique to the gravity with some matter fields, it was shown that there can exist an ambiguity in choosing the counterterms [38,39]. In the holographic Lifshitz theory, for example, there are many different counterterms giving the same UV divergence.…”
Section: Introductionmentioning
confidence: 99%